2009
DOI: 10.1007/s00384-009-0641-2
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of laparoscopic peritoneal lavage for complicated sigmoid diverticulitis

Abstract: We conclude that laparoscopic exploration and peritoneal lavage can be performed safely in patients with diffuse, purulent peritonitis. Using this approach, most patients with purulent peritonitis can avoid emergent laparotomy with the risk of colostomy, and the need for a second surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 23 publications
2
40
0
2
Order By: Relevance
“…Several other non comparative studies that were conducted later showed similar results [13,14,15,16,17,18]. Despite being a relatively small series, our initial experience suggests that despite a high rate of initial success, a significant portion of patients undergoing laparoscopic peritoneal lavage and drainage may suffer from persistent symptoms requiring further surgery with segmental resection.…”
Section: Discussionsupporting
confidence: 62%
“…Several other non comparative studies that were conducted later showed similar results [13,14,15,16,17,18]. Despite being a relatively small series, our initial experience suggests that despite a high rate of initial success, a significant portion of patients undergoing laparoscopic peritoneal lavage and drainage may suffer from persistent symptoms requiring further surgery with segmental resection.…”
Section: Discussionsupporting
confidence: 62%
“…Recent evidence suggests that lavage could be used as a first line in treatment of diverticulitis, if not to cure the disease, at least to prevent a colostomy during subsequent surgery. Also for complications after bowel surgery, lavage is suggested [8][9][10][11][12][13][14][15][16]. RCTs to confirm the beneficial effect of lavage in diverticulitis have been initiated in the Netherlands [23] and in Scandinavia.…”
Section: Discussionmentioning
confidence: 99%
“…Although lavage during laparoscopy is more efficient than during laparotomy [3], its usefulness remains controversial [4][5][6][7]. Over the last years, extensive peritoneal lavage during laparoscopy was reported to be useful for the treatment of complications following colorectal surgery and for diverticulitis [8][9][10][11][12][13][14][15][16]. In animal models, lavage decreases adhesion formation following peritonitis [17].…”
Section: Introductionmentioning
confidence: 99%
“…The first published study of patients undergoing laparoscopic lavage for generalized purulent peritonitis due to perforated diverticular disease reported that all eight patients made a complete recovery, with no patient requiring further surgical intervention in the 12-to 48-month follow-up period [47]. Subsequent small series also concluded that laparoscopic lavage is a safe and effective alternative to colectomy in patients with diffuse purulent peritonitis [48][49][50][51][52][53][54][55]. The largest published series to date included 100 patients with generalized peritonitis and radiological evidence of pneumoperitoneum [56]; 92 of these were managed by laparoscopic lavage, and all eight patients with faecal peritonitis were converted to an open Hartmann's procedure.…”
Section: The Role Of Laparoscopic Peritoneal Lavagementioning
confidence: 99%